2008
DOI: 10.1007/s00395-008-0727-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting matrix metalloproteinase-2 reduces protein release into coronary effluent from isolated rat hearts during ischemia-reperfusion

Abstract: MMP inhibition not only reduces cardiac mechanical dysfunction but also reduces endothelial damage resulting from cardiac I/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 42 publications
4
42
0
1
Order By: Relevance
“…This is the first demonstration that the cardioprotective dose ranges of ilomastat, when administered before ischemia or before reperfusion, were not overlapping in vivo. Our present results are supported by previous studies describing that cardiac mechanical function after ischemia/reperfusion injury via the inhibition of MMP-2 in isolated rat hearts [25,78,79]. We have recently shown that the intravenously injected ilomasat (at 1.5 µmol/kg, administered before the onset of ischemia) decreased infarct size and had a comparable cardioprotective effect to ischemic late preconditioning [36].…”
Section: Study 1: Mmp-2 Inhibition By Ilomasat Exerts Cardioprotectionsupporting
confidence: 91%
“…This is the first demonstration that the cardioprotective dose ranges of ilomastat, when administered before ischemia or before reperfusion, were not overlapping in vivo. Our present results are supported by previous studies describing that cardiac mechanical function after ischemia/reperfusion injury via the inhibition of MMP-2 in isolated rat hearts [25,78,79]. We have recently shown that the intravenously injected ilomasat (at 1.5 µmol/kg, administered before the onset of ischemia) decreased infarct size and had a comparable cardioprotective effect to ischemic late preconditioning [36].…”
Section: Study 1: Mmp-2 Inhibition By Ilomasat Exerts Cardioprotectionsupporting
confidence: 91%
“…This suggests that important role in mechanisms of cardioprotection induced by these different forms of short-term adaptation procedures plays the observed reduction of MMP-2 activities at the beginning of test ischemia. Inhibition of MMP using inhibitors may provide benefits in the treatment of cardiac diseases through protecting cardiac myocytes and also by protecting the integrity of endothelium and possibly intracellular membranes (Fert-Bober et al 2008). To the significant role of MMP-2 in processes associated with I/R point our data showing the time-dependent changes of MMP-2 activities during prolonged ischemia and release of the active enzyme into the effluent during the following reperfusion.…”
Section: Discussionmentioning
confidence: 72%
“…In one study, a 97% decrease in the ratio of oxidized:reduced glutathione, an indicator of reduced oxidative stress, was observed after minocycline treatment [174]. The positive effects of doxycycline on both cardiac function and tissue damage have also been observed in in vitro ischemiareperfusion studies using isolated perfused rat hearts [177,178].…”
Section: Myocardial Infarction and Cardiovascular Diseasementioning
confidence: 89%